The correlation between lightning and various weather parameters in the Padang monsoon system - Ariadi Hazmi; Muhammad Imran Hamid; Rudy Fernandez; Hanalde Andre; Rizki Wahyu Pratama; Primas Emeraldi (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The correlation between lightning and several weather parameters (rainfall, humidity, air temperature, and wind) in Padang from 2016 to 2020 was statistically analyzed. Lightning data and weather parameters were obtained from two electric field mills (EFMs) and the meteorology, climatology, and geophysics agency (BMKG), Indonesia. The study results show that the highest lightning occurred in November during the wet season. The correlation coefficient between lightning and rainfall during the wet and dry seasons was 0.52 and 0.26, respectively. Furthermore, the correlation coefficient of lightning with humidity, air temperature, and wind during the wet and dry seasons was 0.25, 0.06, 0.15, and -0.45, 0.25, -0.02, respectively. These results indicate a strong relationship between lightning and rainfall during the wet season; rainfall is the only primary variable in lightning frequency.